Adsorption of Nickel Ion by Low Cost Carbon-Kinetic, Thermodynamic and Equilibrium Studies - V. Vijayakumaran; S. Arivoli; S. Ramuthai (E-Journal of Chemistry)
A carbonaceous adsorbent prepared from an indigenous waste, by acid treatment was tested for its efficiency in removing nickel ion. The process parameters studied include agitation time, initial metal ion concentration, carbon dose, pH and temperature. The adsorption followed first order reaction equation and the rate is mainly controlled by intraparticle diffusion. Freundlich and Langmuir isotherm models were applied to the equilibrium data. The adsorption capacity (Qm) obtained from the Langmuir isotherm plot were found to around 43 mg/g at an initial pH of 7.0. The temperature variation study showed that the nickel ions adsorption is endothermic and spontaneous with increased randomness at the solid solution interface. Significant effect on adsorption was observed on varying the pH of the nickel ion solutions. The Langmuir and Freundlich adsorption isotherms obtained, positive ΔH0 value, pH dependent results and desorption of metal ions in mineral acid suggest that the adsorption of nickel ion on MCC involves chemisorption as well as physisorption mechanism.